Optimization of collimator angles in dual-arc volumetric modulated arc therapy planning for whole-brain radiotherapy with hippocampus and inner ear sparing - Wuji Sun (Nature Portfolio, 2021)
Abstract To optimize the collimator angles in dual-arc volumetric modulated arc therapy (VMAT) plans for whole-brain radiotherapy with hippocampus and inner ear sparing (HIS-WBRT). Two sets of dual-arc VMAT plans were generated for 13 small-cell lung cancer patients: (1) The collimator angles of arcs 1 and 2 (θ 1/θ 2) were 350°/10°, 350°/30°, 350°/45°, 350°/60°, and 350°/80°, i.e., the intersection angle of θ 1 and θ 2 (Δθ) increased. (2) θ 1/θ 2 were 280°/10°, 300°/30°, 315°/45°, 330°/60°, and 350°/80°, i.e., Δθ = 90°. The conformity index (CI), homogeneity index (HI), monitor units (MUs), and dosimetric parameters of organs-at-risk were analyzed. Quality assurance for Δθ = 90° plans was performed. With Δθ increasing towards 90°, a significant improvement was observed for most parameters. In 350°/80° plans compared with 350°/10° ones, CI and HI were improved by 1.1% and 25.2%, respectively; MUs were reduced by 16.2%; minimum, maximum, and mean doses (D 100%, D max, and D mean, respectively) to the hippocampus were reduced by 5.5%, 6.3%, and 5.4%, respectively; D mean to the inner ear and eye were reduced by 0.7% and 5.1%, respectively. With Δθ kept at 90°, the plan quality was not significantly affected by θ 1/θ 2 combinations. The gamma-index passing rates in 280°/10° and 350°/80° plans were relatively lower compared with the other Δθ = 90° plans. Δθ showed a significant effect on dual-arc VMAT plans for HIS-WBRT. With Δθ approaching 90°, the plan quality exhibited a nearly continuous improvement, whereas with Δθ = 90°, the effect of θ 1/θ 2 combination was insignificant.